PENYULUHAN TENTANG STUNTING PADA BALITA DIDESA LUBUK SUKON KECAMATAN INGIN JAYA ACEH BESAR - Yuli Zuhkrina; Martina; Melia Benita; Nurlaila; Omi Sastika; Sri Eva Ridha (Transpublika Publisher, 2020)
The first day of life is a critical period for the growth and development of children which begins during pre-pregnancy, pregnancy and lactation, this period is known as the First 1000 Days of Life (HPK). The nutritional problem that can occur at this time is stunting (short). The National Strategy for Accelerating Stunting Reduction in Indonesia targets in 2024 that the stunting prevalence rate can be reduced to 14%, this increase is higher than the target of 19% by Bappenas. In 2019, the national stunting prevalence rate fell to 27.67%. Stunting is a health problem that is a priority to create quality Indonesian human resources. The key to the success of stunting prevention can be done through nutritional monitoring and weight measurement of infants and toddlers by health workers and posyandu cadres. Data on the prevalence of stunting in children under five collected by the World Health Organization (WHO) released in 2018 states that Indonesia is included in the third country with the highest prevalence in the South-East Asian Region after Timor Leste (50.5%) and India (38.4%), which is 36.4% (Ministry of Health Data and Information Center, 2018). The stunting prevalence rate in Indonesia is still above 20%, meaning that it has not reached the WHO target of below 20%. Aceh Province is ranked third for stunting, after East Nusa Tenggara (NTT) and West Sulawesi (Sulbar). However, in the last 5 years the Aceh government was able to reduce the prevalence of stunting from 41.2% in 2013 to 37. The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge of stunting, which was in the good category as much as 23 (53,49%). The conclusion is that there is a significant increase in respondents' knowledge after being given counseling.